Sambutan masyarakat terhadap orang kurang upaya : satu persepsi mereka sendiri di pusat pemulihan Samarahan - Hasnah, Mahasan (University Malaysia Sarawak, UNIMAS., 1997)
This research was undertaken to examine the perceptions, opinions or assumptions of disabled people to society's acceptance of them including their family/relatives and other people. Specifically, the research also aims to identify their perception of themselves, job opportunities, education and facilities that provided for the.